Towards a methodology for analysing nineteenth-century collecting journeys of science and empire, with Charles Darwin's activities in Tierra del Fuego as a case study. (29th August 2018) - Owen, Janet
Abstract : The interests of Charles Darwin and Alfred Russel Wallace in natural history and evolution took them to remote parts of the globe on hazardous, multi-sensory journeys that were ultimately about collecting. This paper introduces a methodology for exploring these complex experiences in more detail, informed by historical geography, anthropology, textual analysis and the geo-humanities. It involves looking for evidence of the richly stimulating and often challenging sensory dynamics within which they collected and connected data, observations, images, specimens, memories and ideas. Darwin's exploits in Tierra del Fuego are examined as a case study, with a particular focus on the collection of 'Fuegian' body paints in 1833. This type of analysis provides a fresh insight into the multi-sensory entanglement of encounter with people and place involved in the collecting process. It helps us to understand better the experiences that shaped what was collected and brought back to Britain, and the personal observations associated with these collections that sowed the seeds for Darwin's work on the origin of species.